Effect of lifestyle modification on serum chemerin concentration and its association with insulin sensitivity in overweight and obese adults with type 2 diabetes. (20th June 2013) - Kim, So Hun; Lee, Seung Hwan; Ahn, Ki Yong; Lee, Dong Hoon; Suh, Young Ju; Cho, Soon Gu; Choi, Yun Jin; Lee, Dae Hyung; Lee, Seung Youn; Hong, Seong Bin; Kim, Yong Seong; Jeon, Justin Y.; et al.
Summary Objective Chemerin, a recently identified adipokine, has been linked to adiposity, insulin resistance, metabolic syndrome risk factors and inflammation. Here, we evaluated whether a 12‐week lifestyle intervention in overweight and obese adults with type 2 diabetes could significantly affect the average blood glucose and serum chemerin levels over time. Design Thirty‐five overweight or obese subjects with type 2 diabetes were randomized to receive intensive lifestyle modification including supervised exercise sessions or usual care for 12 weeks. Anthropometric and clinical data were collected before the intervention and after 12 weeks. Results Lifestyle intervention induced a significant decrease in HbA1c (−1·0 ± 0·5 vs 0·1 ± 0·6%, P < 0·001), BMI, total body fat content, serum lipocalin‐2 and chemerin levels (−8·1 ± 21·6 vs + 8·2 ± 15·9 ng/ml, P = 0·021) and a significant increase in VO2max after 12 weeks compared to the usual care group. Baseline chemerin levels were positively correlated with the homoeostasis model of assessment of insulin resistance (HOMA‐IR), fasting insulin and the high‐sensitivity C‐reactive protein (hsCRP) and negatively correlated with insulin sensitivity index (ISI). Changes in the chemerin concentration during 12 weeks were independently negatively correlated with changes in ISI and positively correlated with changes in fasting plasma glucose, total cholesterol and lipocalin‐2 levels. Conclusions A 12‐week intensive lifestyle intervention significantly decreased serum chemerin level compared to usual care. Decrease in serum chemerin level was associated with improved insulin sensitivity, and this may be involved in the beneficial effects of lifestyle intervention in overweight and obese type 2 diabetic patients.